Anti-Convulsant Activity of Soxhlet Leaf Extracts of Ajuga Integrifolia Buch.-Ham. Ex D.Don (Lamiaceae) in Mice - Desalegn T; Engidawork E (Dove Medical Press, 2023)
Tesfaye Desalegn, Ephrem Engidawork Department of Pharmacology and Clinical Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Ephrem Engidawork, Department of Pharmacology and Clinical Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, P. O. Box 9086, Addis Ababa, Ethiopia, Email ephrem.engidawork@aau.edu.etBackground: The leaves of Ajuga integrifolia Buch.-Ham. ex D.Don (Lamiaceae) have long been used as an anti-convulsant remedy in Ethiopian traditional medicine. However, the evidence supporting their use is sparse in the literature. This study was conducted to add to the existing body of knowledge about the anti-convulsant activity of the plant.Methods: The anti-convulsant activity of the extract was investigated in both acute (pentylenetetrazol [PTZ], 80 mg/kg; and maximal electroshock [MES]) and chronic (PTZ, 35 mg/kg) kindling seizure models. For the experimental paradigms, various doses of the extract (100, 200, and 400 mg/kg) were administered. Positive controls received sodium valproate (200 mg/kg) for the PTZ model and phenytoin (25 mg/kg) for the MES model. Parameters including the onset of clonus and duration of hindlimb tonic extension were recorded and compared with controls. Moreover, the total alkaloid, flavonoid, and phenol contents of the extracts were determined.Results: Ethyl acetate extract produced a superior effect among all solvent extracts in both the PTZ and MES models. At all doses, it significantly delayed the mean onset of clonus (p< 0.01) in the PTZ test compared to controls. It also significantly reduced (p< 0.001) the mean duration of hindlimb tonic extension in the MES model. Treatment of mice with 200 mg/kg (p< 0.01) and 400 mg/kg (p< 0.001) of ethyl acetate extract significantly protected against PTZ-induced kindling compared to controls. The leaf was found to contain 10.002± 0.119 mg atropine equivalent per gram of dry extract of alkaloids, 9.045± 0.8445 mg quercetin equivalent per gram of dry extract of flavonoids, and 21.928± 1.118 mg gallic acid equivalent per gram of dry extract of phenols.Conclusion: This study indicated that the plant A. integrifolia has anti-convulsant activity in both acute and chronic models of seizure. This plant represents a potential source for the development of a new anti-epileptic drug for pharmacoresistant epilepsy.Keywords: Ajuga integrifolia, anti-convulsant, epilepsy, kindling, phytoconstituents, seizure